2009
DOI: 10.1152/ajprenal.90662.2008
|View full text |Cite
|
Sign up to set email alerts
|

Organic anion transporter OAT1 is involved in renal handling of citrulline

Abstract: Because citrulline plasma concentration is elevated in kidney failure, citrulline could be a biomarker of renal insufficiency, although the mechanism regulating its disposition in the kidney has not been clarified. In rat kidney slices, citrulline uptake was apparently Na+ dependent, saturable with Km 556 μM, and significantly inhibited by anionic (PAH) and cationic (TEA) compounds, but not by probenecid at 1 mM. Preincubation of kidney slices with glutarate increased citrulline uptake, while such an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In the kidney, Mitsuoka et al (19) identified B(0)AT1 and b(0,ϩ)AT, sodiumindependent and -dependent transporters of citrulline on the apical membrane of cultured rat renal proximal tubular cells. On the basolateral side of the proximal tubules, sodiumindependent transporters are present and OAT1 is the primary basolateral transporter (22). Giusto et al (11) demonstrated a reduction in basolateral OAT1 following renal ischemia-reperfusion injury in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, Mitsuoka et al (19) identified B(0)AT1 and b(0,ϩ)AT, sodiumindependent and -dependent transporters of citrulline on the apical membrane of cultured rat renal proximal tubular cells. On the basolateral side of the proximal tubules, sodiumindependent transporters are present and OAT1 is the primary basolateral transporter (22). Giusto et al (11) demonstrated a reduction in basolateral OAT1 following renal ischemia-reperfusion injury in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The only other proteins known to be inhibited by probenecid are OATs [67]. OAT1 is expressed in the brain [68], but retinal expression in fish has not been assessed.…”
Section: Supporting Informationmentioning
confidence: 99%
“…For example, studies with rat kidney slices found that basolateral L-citrulline uptake was largely due to the Na + -independent organic anion transporter, OAT1. 34 Yet, in studies with rat renal proximal tubular epithelial cells and the human kidney proximal tubular epithelial cell line, HK-2, apical uptake of L-citrulline was shown to be mediated by at least two distinct Na + -dependent transport systems and one Na + -independent transport system. 35 Likewise, studies with Caco-2 cells, a model of human intestinal epithelial cells, found that apical L-citrulline uptake was mediated both by Na + -dependent (via System B (0,+) ) and Na + -independent (via Systems Figure 5 Citrulline uptake in PAECs cultured under normoxic and hypoxic conditions for 24, 48, or 72 h: (A) total uptake; (B) System A-mediated uptake (determined by the use of amino acid competitors to select for System A: glutamine, histidine, threonine, and leucine, amino acids preferentially transported by Systems N, ASC, and L, respectively); (C) System N-mediated uptake (determined by the use of amino acid competitors to select for System N: 2-methylaminoisobutyric acid, leucine, and threonine, amino acids preferentially transported by Systems A, L, or ASC, respectively).…”
Section: Figure 4 (A -D)mentioning
confidence: 99%